The Current Status and Future Direction of Clinical Research in Japan From a Regulatory Perspective - Maeda, Hideki (Frontiers in Medicine, 2022)
In Japan, a law called the Clinical Trials Act went into being effective on April 1, 2018, and clinical research on human subjects conducted in Japan has been undergone major changes. Those other than clinical trials for marketing approval of drugs or medical devices are broadly classified into “specific clinical trials” and others, and regulations have been tightened for each. As a result, clinical interventional study was drastically reduced, and observational clinical study increased. For the observational clinical study, the two previous ethical guidelines were merged into the "Ethical Guidelines for Medical and Biological Research Involving Human Subjects," which was enacted in March 2021. The observational clinical study is now subject to these ethical guidelines. In addition, changes are planned for the Act on the Protection of Personal Information, which greatly affects data collection in clinical research. Clinical research in Japan must be conducted appropriately while adapting to these various changes in the external environment and legal framework. Adapting to these changes is not an easy task, as it requires increased financial and human resources for all stakeholders.